2023
DOI: 10.1161/circulationaha.122.063651
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Shock-Refractory Ventricular Fibrillation During Resuscitation of Out-of-Hospital Cardiac Arrest

Abstract: BACKGROUND: Out-of-hospital cardiac arrest due to shock-refractory ventricular fibrillation (VF) is associated with relatively poor survival. The ability to predict refractory VF (requiring ≥3 shocks) in advance of repeated shock failure could enable preemptive targeted interventions aimed at improving outcome, such as earlier administration of antiarrhythmics, reconsideration of epinephrine use or dosage, changes in shock delivery strategy, or expedited invasive treatments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…One study developed an ECG-based algorithm to predict patients with refractory VF with significant predictive performance (AUC = 0.85 [95% CI, 0.79–0.89]). 10 Another study developed a clinical decision rule that included variables such as bystander AED application, EMS-witnessed arrest, gender, initial rhythm, and time to arrival at the scene. In both studies, arriving at the scene and contacting the patients were essential to predict refractory VF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study developed an ECG-based algorithm to predict patients with refractory VF with significant predictive performance (AUC = 0.85 [95% CI, 0.79–0.89]). 10 Another study developed a clinical decision rule that included variables such as bystander AED application, EMS-witnessed arrest, gender, initial rhythm, and time to arrival at the scene. In both studies, arriving at the scene and contacting the patients were essential to predict refractory VF.…”
Section: Discussionmentioning
confidence: 99%
“…One such study developed a random forest algorithm using ECG data with considerable performance. 10 Another previous study using North American OHCA cohorts developed a clinical decision rule derived from decision tree analysis using data available to emergency medical services (EMS) after obtaining the patient’s initial ECG rhythm. 7 However, there is no such study done using Asian OHCA datasets, and no studies that attempt prediction using information available prior to EMS arrival at scene.…”
Section: Introductionmentioning
confidence: 99%
“…Innovative techniques of real-time ECG processing may predict at the outset of resuscitation which patients are most likely to manifest refractory VF, providing an opportunity for earlier interventions that may improve the course of resuscitation. 45 …”
Section: Current Statementioning
confidence: 99%
“…Artificial intelligence (AI) is rapidly emerging as a powerful tool in various healthcare applications. 3 , 5 , 6 Artificial intelligence ECGs have been used to predict patients with refractory ventricular fibrillation, 7 identify asymptomatic left ventricular dysfunction, 8 and diagnose abnormality. 9 While acknowledging the promise of AI-ECGs, previous studies indicated that explainability was a key limitation of many deep neural network (DNN) models.…”
Section: Introductionmentioning
confidence: 99%